Innovation, Technology and Economic Growth, Do Patent Rights and Technology Exports Influence Economic Growth in Kenya? - Titus Mosoti Ogero; Julia mwende Musyoka (Research Parks Publishers, 2021)
This paper seeks to determine the link between patent protection, technology and the rate of economic growth in the period 1990-2018 using Romer’s model of endogenous growth and Neoclassical model of economic growth. Least squares is used to check for significance of innovation and technology in influencing economic growth. The results show that, innovation (patent rights) and technology (manufactured and high technology exports) are positively important in determining the rate of economic growth in Kenya. From the results, this paper recommends that there is need for government to encourage innovation through providing patent rights as a means of enhancing economic growth through innovation in new methods and technologies in production and service offering. As well, the government should embrace technology as means of expanding on returns to scale on resources, hence, economic growth.